Laparoscopic Resection of An Extensive Tuboovarian Abscess in A Mechanical Valve Replacement Woman - Phornsawan Wasinghon; Kuan-Gen Huang (Gynecology Obstetrics & Reproductive Medicine)
The case is a 44-year-old-female who presented with right lower abdominal pain without fever or leukocytosis. She had previous mechanical valve replacement with taking warfarin for last ten months from the diagnoses of infective endocarditis. The ultrasonography showed bilateral complex ovarian mass. At laparoscopy, the patient had a right tubo-ovarian abscess and a left mature teratoma with extensive adhesions to the rectum. A case illustrates an uncommon premenopausal age with right tuboovarian abscess and left mature teratoma. The laparoscopic surgery is an excellent benefit for quicker recovery time, smaller incisions, less post-operative pain, and especially of a few infections that will affect to underlying disease of the patient.